2005
DOI: 10.1104/pp.104.058982
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Soluble β-Carbonic Anhydrase in the Marine Diatom Phaeodactylum tricornutum. Sorting to the Chloroplast and Cluster Formation on the Girdle Lamellae  

Abstract: A b-carbonic anhydrase (CA) in the marine diatom Phaeodactylum tricornutum (PtCA1) is encoded by the nuclear genome. This enzyme was previously found to be important for the operation of photosynthesis with a high affinity for dissolved inorganic carbon. A cDNA sequence that encodes PtCA1 (ptca1) was shown to possess a presequence of 138 bp (pre138), which encodes an N-terminal sequence of 46 amino acids (Pre46AA) that does not exist in the mature PtCA1. In this study, pre138 was ligated with the enhanced gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 33 publications
5
88
0
Order By: Relevance
“…Numerous CAs, a critical CCM component, were also found in the genomes of P. tricornutum and T. pseudonana and most of them have been localized Tanaka et al, 2005;Tachibana et al, 2011;Samukawa et al, 2014). Interestingly, there are significant differences in the location of CAs between these two species.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous CAs, a critical CCM component, were also found in the genomes of P. tricornutum and T. pseudonana and most of them have been localized Tanaka et al, 2005;Tachibana et al, 2011;Samukawa et al, 2014). Interestingly, there are significant differences in the location of CAs between these two species.…”
mentioning
confidence: 95%
“…PtCA2 is a paralogous CA to PtCA1, with an approximately 80% amino acid sequence identity whose transcription is also CO 2 -responsive, and they colocalize at the pyrenoid of P. tricornutum Tanaka et al, 2005;Tachibana et al, 2011). Both CAs are under redox regulation by the function of diatom plastidic thioredoxins (Kikutani et al, 2012) and the function of the promoters of both CA genes are responsive to CO 2 via the function of cAMP ( Fig.…”
Section: Truncation Assay Of Pptca2mentioning
confidence: 99%
“…The use of molecular and genetic approaches to study inorganic carbon metabolism and CCMs in other unicellular freshwater and marine algae has revealed an incredible diversity of carbonic anhydrases representing all known classes of these enzymes (12,15,18,19,30,35,39,43). For example, the green alga Chlamydomonas reinhardtii possesses six CAs representing two classes (␣ and ␤) with distinct cellular locations: the periplasm (Cah1 and Cah2), thylakoid lumen (Cah3 and Cah6), and mitochondria (ca1 and ca2) (19).…”
mentioning
confidence: 99%
“…A b-carbonic anhydrase in the marine diatom P. tricornutum (PtCA1), thought to be one of the crucial chloroplastic components of the CCM (Satoh et al, 2001;Tanaka et al, 2005), is known to be regulated strictly by the ambient [CO 2 ] and light . A promoter region of the PtCA1 gene (ptca1) was isolated previously, and it was demonstrated that the critical CO 2 -response sequence was located downstream 270 bp relative to the transcription start site .…”
mentioning
confidence: 99%